2002
DOI: 10.4049/jimmunol.169.10.5477
|View full text |Cite
|
Sign up to set email alerts
|

The Osmoprotective Function of the NFAT5 Transcription Factor in T Cell Development and Activation

Abstract: The NFAT5/TonEBP transcription factor, a recently identified rel/NF-κB family member, activates transcription of osmocompensatory genes in response to extracellular hyperosmotic stress. However, the function of NFAT5 under isosmotic conditions present in vivo remains unknown. Here we demonstrate that NFAT5 is necessary for optimal T cell development in vivo and allows for optimal cell growth ex vivo under conditions associated with osmotic stress. Transgenic mice expressing an inhibitory form of NFAT5 in devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
105
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 42 publications
11
105
1
Order By: Relevance
“…Several data presented here illustrate the physiological significance of NFAT5 for cell survival in cardiac myocytes, consistent with previous reports concerning the cytoprotective roles of the transcriptional targets of NFAT5 in mammalian cells (16,19,20). TauT is a major factor in maintaining a high gradient of cardiac tissue/plasma taurine concentration (46,47).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Several data presented here illustrate the physiological significance of NFAT5 for cell survival in cardiac myocytes, consistent with previous reports concerning the cytoprotective roles of the transcriptional targets of NFAT5 in mammalian cells (16,19,20). TauT is a major factor in maintaining a high gradient of cardiac tissue/plasma taurine concentration (46,47).…”
Section: Discussionsupporting
confidence: 76%
“…Expression vector of truncated NFAT5 construct consists of a DNA-binding domain (212-543 amino acids) as described previously (10). Other investigators have revealed that the deletion mutant inhibits endogenous NFAT5 activity, interfering with NFAT5 dimerization but not the transcriptional activity of the other NFATs, NF B and AP-1 (16,25).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The release of and response to ATP plays a key role in the mechanism through which hypertonic stress regulates the function of T cells [26]. NFAT5 is also necessary for optimal T-cell development in vivo and allows for optimal cell growth ex vivo under conditions associated with osmotic stress [27]. Furthermore, William Go and his co-workers [21,28] measured lymphoid tissue osmolality directly by using a vapor pressure osmometer and they found that in contrast to brain and lung, lymphoid tissues were significantly hypertonic relative to serum.…”
Section: Discussionmentioning
confidence: 99%